2016
DOI: 10.1515/jomb-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of LncRNA HULC Enhances Chemotherapy Induced Apoptosis in Human Gastric Cancer

Abstract: SummaryBackgroundGastric cancer (GC) is one of the most common cancers in the world; however, chemoresistance greatly decreases the efficacy of therapy in gastric cancer. Long noncoding RNAs (IncRNAs) participate in a variety of biological processes, and we hypothesize that lncRNA HULC regulates the multidrug resistance in GC treatment.MethodsWe obtained GC tissue samples from 42 GC patients and detected the expression level of HULC in the plasma and tissues via qRT-PCR. The relationship between HULC expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…HULC is a long non-coding RNA that has been identified as a driver of tumorigenesis in multiple cancers [37,38,39], including liver cancer, osteosarcoma, cervical cancer, pancreatic, stomach and ovarian cancers [40,41,42,43,44,45]. HULC expression is a predictor of poor prognosis across multiple cancers [46,47,48,49], and HULC silencing enhanced the effectiveness of chemotherapy in stomach cancer cell lines [44]. The involvement of HULC in the tumorigenesis of a subset of NRAS mutant melanomas appears to be unreported and merits further investigation as a possible novel discovery with therapeutic implications.…”
Section: Novel Melanoma Combinations Detected By Crsomentioning
confidence: 99%
“…HULC is a long non-coding RNA that has been identified as a driver of tumorigenesis in multiple cancers [37,38,39], including liver cancer, osteosarcoma, cervical cancer, pancreatic, stomach and ovarian cancers [40,41,42,43,44,45]. HULC expression is a predictor of poor prognosis across multiple cancers [46,47,48,49], and HULC silencing enhanced the effectiveness of chemotherapy in stomach cancer cell lines [44]. The involvement of HULC in the tumorigenesis of a subset of NRAS mutant melanomas appears to be unreported and merits further investigation as a possible novel discovery with therapeutic implications.…”
Section: Novel Melanoma Combinations Detected By Crsomentioning
confidence: 99%
“…LncRNAs are demonstrated to pose significant effects on the cancer-related metabolism, such as lipid metabolism and glycolysis, in a variety of cancer types 39,40 . Also, accumulating studies have attributed the development of chemo-resistance to aberrant expression of certain lncRNAs 37,38 . These discoveries suggested that MSCs might regulate chemoresistance in GC through altering expressions of lncRNAs, specifically the lncRNAs related to metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HOTAIR/miR-17-5p/ PTEN axis regulates the chemo-sensitivity in GC 37 . Knockdown of HULC facilitates apoptosis and alleviates chemo-resistance in GC 38 . SNHG16 facilitates colorectal cancer progression through participating in lipid metabolism 39 .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA SNHG5 reduced DDP sensitivity of BGC823 and SGC7901 gastric cancer cells through up-regulating expression of MDR1, MRP1 and Bax as well as downregulating Bcl-2 expression [164]. In addition, lncRNAs GHET 1 [165], AK022798 [166], antisense non-coding RNA in the INK4 locus (ANRIL) [167], UCA 1 [168] and HULC [169] also conferred DDP resistance of gastric cancer cells via modulating expression of multiple drug resistance-related genes. LncRNA HOTAIR, which was significantly up-regulated in DDPresistant gastric cancer cells and tissues, could regulate chromatin status and contribute to DDP resistance of gastric cancer, through activating PI3K/Akt/MRP1 and Wnt/ β-catenin signaling pathways [170,171].…”
Section: Lncrnas and Resistance To Platinum Drugsmentioning
confidence: 99%